If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(f+-7)=6
We move all terms to the left:
2(f+-7)-(6)=0
We add all the numbers together, and all the variables
2(f-7)-6=0
We multiply parentheses
2f-14-6=0
We add all the numbers together, and all the variables
2f-20=0
We move all terms containing f to the left, all other terms to the right
2f=20
f=20/2
f=10
| –7+u6=0 | | -4(f+1)=12 | | (5x-4)(2x-7)=0 | | b=40-9b | | 12+y3=15 | | 25=k÷5 | | 12+5t=4t | | -6(1-m)=0-2m | | 1/4k-6=3 | | -4(4x+5)=124 | | 45=(2w+1)w | | 47=10r+17 | | -5(-1+5x)=-20 | | 6m-3+7=9 | | 5(4-6x)=170 | | -10x+4=-8x | | 3-2/b=1/3bb-7 | | 7h=-1(2h+18) | | x/465.3=16.5 | | 20=n/611 | | x/16.5=465.3 | | 4/n−2=5 | | 7k/3=27 | | r+6r+6-5r=14-2r | | 5/m−3=8 | | 1/3x+1/4=-3(5/6x-1) | | –z/3–9=–7 | | 0/4t=0.72 | | 341=5y | | 7x-12x-1=-26 | | -2x+6=5x-7 | | –z3–9=–7 |